Influence of Extremophiles on the Generation of Acid Mine Drainage at the Abandoned Pan de Azúcar Mine (Argentina) - Josefina Plaza-Cazón; Leonardo Benítez; Jésica Murray; Pablo Kirschbaum; Edgardo Donati (Microorganisms, 2021)
The risk of generation of acid drainages in the tailings of the Pan de Azúcar mine that closed its activities more than three decades ago, was evaluated through biooxidation studies using iron- and sulfur-oxidizing extremophilic leaching consortia. Most of tailings showed a high potential for generating acid drainage, in agreement with the results from net acid generation (NAG) assays. In addition, molecular analysis of the microbial consortia obtained by enrichment of the samples, demonstrated that native leaching microorganisms are ubiquitous in the area and they seemed to be more efficient in the biooxidation of the tailings than the collection microorganisms. The acid drainages detected at the site and those formed by oxidation of the tailings, produced a significant ecotoxicological effect demonstrated by a bioassay. These drainages, even at high dilutions, could seriously affect a nearby Ramsar site (Laguna de Pozuelos) that is connected to the Pan de Azúcar mine through a hydrological route (Cincel River).